Using business process reengineering to obtain a RAISE specification - Riesco, Daniel Eduardo (2002)
We have proposed a technique which can be employed within the methodology known as business process reengineering. This technique has been applied in a government project, which included an Information System and Geographical Information System, developed with financial support from The World Bank. One model used in process reengineering is the process model diagram, which helps to find the tasks, to be completed in each area of the organisation. To understand the domain is crucial to be able to specify each one of these tasks. We show in this work how to use process modelling to find the tasks and to formalise their description using RAISE formal method. In this way, using a model of process as input, an engineer employs a systematic technique to create-as a starting point-the main functions (tasks) of the domain using the RAISE formal method. Furthermore, we show how a structured architecture in layers can be used for reuse during the development in the large.